PENINGKATAN PRESTASI BELAJAR MATA KULIAH DASAR-DASAR AKUNTANSI MELALUI PENERAPAN MODEL JIGSAW - Sumaryati, Sri; Ulfa, Laili Faiza (Universitas Sebelas Maret, 2010)
The purpose of this research is: (1) to get abiliti’s learning model is cooperativelearning jigsaw, (2) to get abiliti's lecture to fixed strategy and variaty learning model,(3) to get abiliti's student to reserve and to understanding subject Principle of Accoun-ting. The result of the research shows that: (1) the using method of cooperative jigsaw inprocess to learn and teaching in accounting, spesifically in subject accounting of tradingfirm can reach activity fisically and mental of student via more activities in processlearning; (2) the using method of cooperative jigsaw in process to learn and teaching inaccounting, to reach succes in study and students can learn to finally, this is can be see inaverage of class from Quiz I was 65,00 and Quiz II was 77,24.